(untitled) (MedS Alliance Journal of Medicine and Medical Sciences, 2023)
INTRODUCTION: Malocclusion is defined as an irregularity concerning teeth alighnment and/ or their relationship during dental occlusion beyond the range of what is accepted as normal.The study was conducted in order to identify prevalence of malocclusion in adolescents visiting dental department of a tertiary care centre at Dhanusha district of Madhesh Pradesh. MATERIALS AND METHODS: A descriptive cross-sectional study was conducted at Out-Patient Department of dental department of Janaki Medical College and Teaching Hospital (JMCTH) with participants aged 13-19 years irrespective of gender. Total of 600 adolescents were examined for malocclusion like overjet,overbite,spacing,crowding,rotation and missing tooth. Angle’s Classification was used to define malocclusion in participants. RESULTS: 93.8% of participants had some sort of malocclusion. Highest prevalence of Angle’s Class I(68%) followed by Class II(21.3%) and Class III(4.5%) was found.40.5% had increased overjet, 33.5% have deep overbite and 31.2% have crowding. 37.25% of participant had rotation of tooth. CONCLUSIONS: The study concludes with the fact that Angle’s Class I Malocclusion is the major malocclusion presenting in OPD of JMCTH. High percentage of adolescents with permanent dentition having some sort of malocclusion also seems to be concern which can affect future self confidence and much more expenditure on treatment and maintenance.